2020
DOI: 10.3390/s20051524
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Strategy for Electrochemical Sensing of Carbaryl Residue in Water and Vegetable Samples

Abstract: Accurate analysis of pesticide residue in real samples is essential for food safety and environmental protection. However, a traditional electrochemical sensor based on single-signal output is easily affected by background noise, environmental conditions, electrode diversity, and a complex matrix of samples, leading to extremely low accuracy. Hence, in this paper, a ratiometric strategy based on dual-signal output was adopted to build inner correction for sensing of widely-used carbaryl (CBL) for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The oxidation of CBR in the presence of Ag/ZnO NCs was proposed by two processes as follows: 11,49,50 (1) In alkaline media with adding of NaOH, CBR molecules were hydrolyzed to 1-naphthol.…”
Section: Effect Of Crystallinity and Size Distribution Of Bio-ag/zno ...mentioning
confidence: 99%
“…The oxidation of CBR in the presence of Ag/ZnO NCs was proposed by two processes as follows: 11,49,50 (1) In alkaline media with adding of NaOH, CBR molecules were hydrolyzed to 1-naphthol.…”
Section: Effect Of Crystallinity and Size Distribution Of Bio-ag/zno ...mentioning
confidence: 99%
“…Although the proposed e-GCE CP−CV was not sensitive toward the group of −OH, many other modified electrodes could largely enhance this oxidation peak current but fail to distinguish each of the carbamate insecticides. 34,35 However, compared with other carbamate insecticides with one benzene ring, the hydrolyzed product of 1-naphthol from CBL with two benzene rings has active chemical properties that it can be transformed into various derivatives through electrochemical regulation, 33,36,37 and is more likely to be adsorbed on the surface of the carbon-based electrode via the π−π bond. As mentioned above, 1-naphthol could be transformed to 1,4-naphthoquinone on the surface of proposed e-GCE CP−CV during the facile process of regulation III, giving rise to a reduction peak at −0.25 V. In that case, the constructed sensor can avoid interference of other carbamate insecticides by detecting the electrochemical signal of the specific derivative.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, enzymes employed as sensors require specific handling in terms of storage, temperature, enzyme activity, pH and applied potential, which makes these devices more complicated to deal with and less consistent in terms of reliability [ 11 ]. Recently, non-enzymatic methods have been reported which require the hydrolysis of carbaryl to carbaryl–phenol ( Figure 1 ) to enhance the electrochemical reaction [ 12 , 13 ]. However, it was reported that carbamate residues can be detected directly, electrochemically, without the requirement for the target analytes to be first hydrolyzed [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%